Formas cotidianas de participación política rural : el Procede en Yucatán - Torres Mazuera, Gabriela (El Colegio de México, 2014)
Yucatan stands out as the federal state with the highest percentage of indigenous population where the Procede program was better accepted, but where ejidatarios decided to maintain the common lands without division. The opposition to ejido lands division in this context has been interpreted by many analysts as an indigenous resistance to privatization of ejido lands and more broadly to the modernization project launched with Article 27 reform. The objective of this paper is threefold: first to identify other factors besides the ethnic component, that combined may explain the specific responses ejidatarios in Yucatan gave to Procede. Second, to explore the variety of responses given by Yucatan ejidatarios to this program, which includes not only resistance but collaboration. Finally, my aim is to show that contrary to the expectations of program designers and more broadly of the 1992 Land reform Law promoters, one of the Program unforeseen results has been the emergence, within ejidos, of new types of irregular and illegal practices.